EVALUATION OF FACTORS INFLUENCING EFFICIENCY OF COCOYAM PRODUCTION AMONG FARMERS IN EKITI STATE - Faleye, O.O.; Ajiboye, A.J.; Agunbiade, B.O.; Ogunniyi, G.; Adekanye, J.O.; Aruleba, S.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analyses the factors influencing the efficiency of cocoyam production among farmers in Ekiti State. A multi-stage sampling procedure was employed to select 224 respondents for the study. Primary data were collected with the use of well-structured questionnaires comprised of open and close-ended questions. The collected data were analysed using both descriptive statistics and the stochastic production frontier function. The results show that 67.41% of the respondents in the study area were male, with a mean age of 37 years, and a higher proportion (76.43%) being above 30 years. The respondents were fairly literate, with 75.00% who had more than 5 years of experience in cocoyam production. The average farm size was 3.9 hectares. Technical efficiency analysis indicated that 26.3% of respondents had technical indexes between 0.91 and 1.00, with a mean technical efficiency of 0.79. The estimated coefficients of factors such as land area, herbicide, and fertilizer use had significant (p<0.05) effects on yield, suggesting their potential to increase cocoyam yield. However, increasing the number of suckers and pesticides did not enhance yield, leading to decreased efficiency. Additionally, factors like age, gender (more female), and cooperative membership were found to reduce efficiency as they increased. Conversely, farming experience and family size had negative relationship with inefficiency, indicating that higher levels of these factors improved overall efficiency. The study therefore recommends amongst others that more arable land should be provided in the study area to maximize the use of labour and further enhance the efficiency of cocoyam farmers.